Muscle mass index estimated by anthropometry vs bioelectrical impedance: Study in athletes competing by weight categories - Canda, A. S. (Apunts Sports Medicine, 2021)
The aim of the study was to compare the muscle mass obtained by anthropometry and bioelectrical impedance, in athletes competing by weight categories. 109 (42 women y 67 men), age 21.4 ± 3.5 years, boxing (32), weightlifting (16), judo (28), karate (12), fighting (14) and taekwondo (7) practitioners were selected. The protocol included nineteen anthropometrics variables and a bioelectrical impedance analysis (akern®), estimating the muscle mass by anthropometry by the Lee's equation (2000) and by bioimpedance by Janssen's equation (2000), calculating the muscle mass index (IMM, kg/m2). In ten athletes it was examined whether in a second exploration the changes over time were similar by both techniques. The intraclass correlation coefficient (ICC) and the Bland-Altman analysis were applied to assess the concordance. Results: The IMM estimated by Lee vs Janssen, was in the female sample, 9.01 ± 1.01 kg/m2 vs 8.68 ± 1.1 kg/m2; and in the male sample, 11.17 ± 1.34 kg/m2 vs 11.04 ± 1.13 kg/m2 .The ICC was 0.945 [95%IC; 0.915-0.964]. The difference in the IMM between both techniques was 0.21; with a confidence range of 95% between +1.60 a -1.18. In the longitudinal study, five of the athletes controlled (50%), gave differences in the assessment of their IMM's changes. We concluded that even though in a statistical sense there is a high concordance between both equations being valid for epidemiological studies, the differences found cannot be assumed as interchangeable for the individual assessment of each athlete nor in comparative studies.